Why we believe in “Better health by design” - Editor JHD (The Journal of Health Design, 2019)
The journal's tagline “better health by design” encapsulates our efforts to achieve better health outcomes through better design of physical structures, processes, and technologies; better access to services and providers; and creating a more meaningful connection through deep listening and active engagement.